Pulmonary dirofilariasis: report of a human case. - Leonardi, H K (1977)
Dirofilaria immitis (dog heartworm) principally infests canine hosts. However, human pulmonary dirofilariasis is being reported with increasing frequency, and the following case illustrates essential features of the disease. It typically presents as a solitary pulmonary nodule without symptoms and invariably requires pulmonary resection to differentiate it from primary or secondary malignancy.